USE OF REFLEXOTHERAPY IN THE REHABILITATION OF CHILDREN'S BRONCHIALASTMA DISEASE - Markhabo T. Okhunova; Kuat K. Mnajov; Dilrabo Sh. Maxsudova (Journal Park Publishing, 2025)
The incidence of bronchial asthma is increasing worldwide. According to the data collected in Uzbekistan, diseases of the respiratory organs are currently in one of the most important places in the country. The incidence has increased 2.5 times over the past five years. According to statistics, 10% of people suffer from this disease. Bronchial asthma occurs at any age and any gender. But mostly boys are hit more often than girls. (Sergeeva G.R., Emelyanov A.V., Leshenkova E.V., Znakhurenko A.A., 2020). Consider adding reflexology, a non-traditional method of treatment for bronchial asthma in children.
Keywords: Children, bronchial asthma, reflexotherapy, medical rehabilitation.